International Finance and New York: Role of Outlaw of Private Financial Capital from United States in Determination of Significance of New York as Center of International Finance - Nordyke, James W. (Journal of Finance, 1960)
James W. Nordyke, International Finance and New York: Role of Outlaw of Private Financial Capital from United States in Determination of Significance of New York as Center of International Finance, The Journal of Finance, Vol. 15, No. 1 (Mar., 1960), pp. 86-87